Antibacterial activity and therapeutic efficacy of Fl-PRPRPL-5, a cationic amphiphilic polyproline helix, in a mouse model of staphylococcal skin infection - Thangamani S; Nepal M; Chmielewski J; Seleem MN (Dove Medical Press, 2015)
Shankar Thangamani,1 Manish Nepal,2 Jean Chmielewski,2 Mohamed N Seleem11Department of Comparative Pathobiology, Purdue University College of Veterinary Medicine, West Lafayette, IN, USA; 2Department of Chemistry, Purdue University, West Lafayette, IN, USAAbstract: The antibacterial activities and therapeutic efficacy of the cationic, unnatural proline-rich peptide Fl-PRPRPL-5 were evaluated against multidrug-resistant Staphylococcus aureus in a mouse model of skin infection. Fl-PRPRPL-5 showed potent activity against all clinical isolates of S. aureus tested, including methicillin- and vancomycin-resistant S. aureus (MRSA and VRSA, respectively). Fl-PRPRPL-5 was also superior in clearing established in vitro biofilms of S. aureus and Staphylococcus epidermidis, compared with the established antimicrobials mupirocin and vancomycin. Additionally, topical treatment of an MRSA-infected wound with Fl-PRPRPL-5 enhanced wound closure and significantly reduced bacterial load. Finally, 0.5% Fl-PRPRPL-5 significantly reduced the levels of the inflammatory cytokines tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and interleukin-1 beta (IL-1β) in wounds induced by MRSA skin infection. In conclusion, the results of this study suggest the potential application of Fl-PRPRPL-5 in the treatment of staphylococcal skin infections.Keywords: antimicrobial peptides, Staphylococcus aureus, biofilms, anti-inflammatory, skin infection